Ação de antibióticos e quimioterápicos sobre alguns agentes baxterianos da mastite bovina, isolados da água utilizada no processo de obtenção do leite - Amaral, L. A.; Nader, A.; Rossi, O. D.; Penha, LHC (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1996)
Three strains of Staphylococcus aureus, 73 coagulase negative Staphylococcus and 28 Escherichia coli strains,isolated from water samples from 10 dairy farms, were tested for ''in vitro'' sensitivity to antibiotics and chemotherapeutics. The results showed that all samples isolated presented resistance to at least one active drug tested. The percentage of S. aureus, coagulase negative Staphylococcus and E. coli strains that exhibited resistance to the three active drugs were 100.00%, 84.93% and 71.43%, respectively. These results are important mainly due to the role of water as a vehicle for transmission of mastitis bacterial agents during the milking process.
Action of antibiotics and chemotherapics on some bacterial agents of bovine mastitis isolated from water utilized in the milking process
Keywords: water; Staphylococcus aureus; coagulase negative Staphylococcus; Escherichia coli; bovine mastitis